Set on noteS: Palindromes and Other Symmetry in the Music of Viktor Ullmann - Rachel Bergman (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2013)
Viktor Ullmann (1898–1944), a pupil of Arnold Schoenberg, not only studied with the Viennese master but also developed significant personal and professional relationships with many of those closely associated with him, most notably Alexander Zemlinsky and Alban Berg. Evidence of the far-reaching influence of Schoenberg and his circle is found in Ullmann’s creation of coherence and structure through symmetry—a primary unifying feature throughout his music. While he grappled with issues of tonality and atonality, varying the extent to which he integrated the two, he remained consistent in using symmetry throughout his ouevre. We see symmetry playing a role in his earliest works, represented by the Variationen und Doppelfuge über ein Thema von Arnold Schoenberg of 1925; his middle-period works, including the first and third piano sonatas (1936 and 1940, respectively); and the Theresienstadt works, including the melodrama Die Weise von Liebe und Tod des Cornets Christoph Rilke and Piano Sonata No. 7 (both written in 1944, the year of his death). The most significant type of symmetry found consistently in Ullmann’s music is “mirror” symmetry, which is created about a specific focal pitch or pair of pitches. This symmetry typically works in pitch space, both on the surface and as larger structural features of Ullmann’s music. An exploration of Ullmann’s use of symmetry, specifically in the context of the Second Viennese School, not only demonstrates the impact of Schoenberg and his circle but—more importantly—reveals how Ullmann’s use of symmetry is distinct from that of his models. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part IV).